Aulularia and other Inversions of Plautus : Aulularia and other Inversions of Plautus - Burmeister, Joannes, 1576-1638 (Bibliotheca Latinitatis novae, 2015)
First critical edition of Burmeister's newly discovered Aulularia. Joannes Burmeister of Lüneburg (1576-1638) was among the greatest Neo-Latin poets of the German Baroque. His masterpieces, now mostly lost, are Christian 'inversions' of the Classical Roman comedies of Plautus. With only minimal changes in language and none in meter, each transforms Plautus's pagan plays into comedies based on biblical themes. Fascinating in their own right, they also bring back to attention forgotten genres of Renaissance literature. This volume offers the first critical edition of the newly discovered Aulularia (1629), which exists in a sole copy, and the fragments of Mater-Virgo (1621), which adapts Plautus's Amphitryo to show the Nativity of Jesus. The introduction offers reconstructions of Susanna (based on Casina) and Asinaria (1625), Burmeister's two lost or unpublished inversions of Plautus. Fontaine also provides the only biography of Burmeister based on archival sources, along with discussions of his inimitable Latinity and the perilous context of war and witch-burning in which Burmeister wrote. Burmeister's inversions bear witness to the special talent of his age for the creative reworking of Classical literature, such as Monteverdi's Poppea or Purcell's Dido and Aeneas, as well as to his tumultuous times, with his views on military abuses in the Thirty Years' War prefiguring those of Grimmelshausen's Simplicius Simplicissimus.